Integration of crop-specific and validated seasonal climate and weekly agro-advisories into Laos Climate Services for Agriculture (LaCSA) for farmers at provincial and district-levels disseminated through various formats and communication channels - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Operational in five provinces where FAO-Strengthening Agro-climatic Monitoring and Information System (SAMIS)project is working and LaCSA system is available. DeRISK developed a mobile application using Kobo and piloted to collect field-data to provide near real-time information on crop conditions (crop-stage, water-stress, cultural management) to support tailoring of climate and agro-advisory.